Transcriptomic analysis of small intestinal mucosa from porcine epidemic diarrhea virus infected piglets. (July 2019) - Sun, Pei; Fahd, Qarih; Li, Yezhen; Sun, Yao; Li, Jie; Qaria, Majjid A.; He, Zhan Song; Fan, Yuzhen; Zhang, Qiang; Xu, Qianming; Yin, Zongjun; Xu, Xingang; et al.
Abstract: Caused by porcine epidemic diarrhea virus (PEDV), porcine epidemic diarrhea (PED) is an acute infectious disease which causes damage to the intestine including intestinal villus atrophy and shedding, leading to serious economic losses to the pig industry worldwide. In order to obtain detailed information about the pathogenesis and host immune response in a PEDV-infected host for first In vivo study we used high-throughput sequencing to analyze the gene expression differences of the small intestinal mucosa after infection with PEDV. Transcripts obtained were over 65, 525, 000 clean reads after reassembly were 22, 605 genes detected, of which 22, 248 were known genes and 371 new genes were predicted. Moreover, 3168 genes expression was up-regulated and 3876 genes down-regulated. (Gene Ontology) GO annotation and functional enrichment analysis indicated that all of the DEGs (differentially expressed genes) were annotated into biological process, cellular component and molecular function. Most of these unigenes are annotated in cellular processes, the cell and binding. KEGG analysis of the DEGs showed that a total of 7044 DEGs unigenes were annotated into 323 pathways classified into 6 main categories. Most of these unigenes are annotated were related to immune system response to the infectious diseases pathways. In addition, 20 DEGs were verified by quantitative real-time PCR. As the first, in vivo, RNAseq analysis of piglets and PEDV infection, our study provides knowledge about the transcriptomics of intestinal mucosa in PEDV-infected piglets, from which a complex molecular pathways and pathogenesis-related biological processes are involved in PEDV interaction with piglet intestinal mucosa. Highlights: Within vivo RNAseq analysis, the mapping rate of PEDV infected piglets was 93.55%, 22, 248 known genes and 371 novel genes. 3168 genes were up-regulated and 3876 genes were down-regulated compare to uninfected piglets. Most of expressed genes were related to immune system followed by endocrine system. TLRs expression were elevated in the PEDV infected piglets and induced subsequent downstream signaling pathways.